Evaluating energy generation potential from municipal solid waste in an open dumping site of Khulna - Saptarshi Mondal; Islam M. Rafizul (City and Environment Interactions)
The expanding global population, waste output, land scarcity, and environmental deterioration make waste-to-energy (WtE) technology a feasible option for managing MSW. This study explores the economic benefits of WtE in the Rajbandh open dumpsite in Khulna and the potential of generating energy from MSW. The electricity generation potential under alternative scenarios namely scenario 2 (landfill gas to electricity (LFGTE)), scenario 3 (mass-burn incineration), scenario 4 (hybrid LFGTE, mechanical–biological treated (MBT) anaerobic digestion (AD) and incineration), and scenario 5 (hybrid AD and refuse-derived fuel (RDF) incineration) is based on projected waste generation over the next 20 years, taking population growth into account. These four options are compared to Business as Usual (BAU). Scenario 3 has the highest electricity generation capacity at 207799.73 MWh/year, followed by hybrid RDF-incineration/MBT-AD (scenario 5), LFGTE, however, lowest generation at 30683.07 MWh/year. Net Present Value (NPV), Levelized Cost of Electricity (LCOE), and Payback Period define each scenario’s economic feasibility. Due to its greatest NPV of approximately 41.378 million USD, Scenario 3 is the most economically beneficial. Sensitivity analysis has been done selecting some sensitive parameters to evaluate the robustness of the output. Waste reduction model (WARM) estimates greenhouse gas (GHG) emissions and energy use for each scenario. However, scenario 3 has the lowest GHG emissions and energy use. In addition to reducing GHG emissions and energy usage, recycling waste increased NPV and economic benefits. This analysis reveals that scenario 3 is the best way to generate power, provide economic benefits, and reduce energy consumption for ecologically friendly waste management in Khulna City.